PTH-099 Vitamin D levels in coeliac disease: do they warrant monitoring?. (23rd September 2015) - Joshi, N M; Aljabiri, M R; Fuller, L; Butcher, C; Ifijen, M; Good, E; Ramdass, D; van Someren, N; Besherdas, K
Abstract : Introduction: Coeliac disease is a lifelong inflammatory condition affecting the small bowel. Treatment involves a strict gluten free diet that should be supervised by a dietician. Follow-up is important because of potential long-term complications. The British Society of Gastroenterology (BSG) coeliac guidelines say that with a satisfactory response to diet, specialist outpatient follow-up should be at 6–12-month intervals to assess symptomatic improvement, nutritional state, dietary compliance and to check routine blood tests. Coeliacs are predisposed to metabolic bone disease and current guidelines recommend measuring bone mineral densitometry in all coeliacs. Vitamin D deficiency can also lead to metabolic bone disease and as coeliacs are predisposed to fat malabsorption they are also at risk of being vitamin D deficient and hence at further risk of developing bone de-mineralisation. Checking vitamin D levels is not mentioned in the BSG guidance on management of coeliacs and hence, it is not routinely measured. If vitamin D deficiency is noticed, simple replacement would further minimise the chance of developing osteopaenia/osteoporosis. Methods: A single centre retrospective analysis of coeliac disease patients under follow-up was performed. Vitamin D levels were measured as part of routine blood test monitoring at follow-up in coeliac clinic. As some of these patients were also on combined calcium and vitamin D replacement, this was also taken into account. The resulting data were then analysed. Our laboratory vitamin D reference range is 47–144 ng/ml. Results: 56 patients (12 male) attended follow-up in the study period with an average age of 62.7 years (22–90 years). The average vitamin D level was 73.2 ng/ml (15–153 ng/ml). 9 (16.7%) patients, all female, were vitD deficient with an average vitD level of 27.5 ng/ml (15–46 ng/ml). Further results of the nine patients with VitD deficiency are summarised in Abstract 099 . Conclusion: 16.7% of coeliac patients in this study have vitamin D deficiency. Monitoring vitamin D levels is easy and we advocate measuring vitamin D levels in all coeliac patients in view of enhanced risk of developing osteoporosis. Monitoring of vitamin D should be included in any national guideline on management of coeliac disease. We further promote dieticians to council patients on increasing the vitamin D in their diets when discussing gluten free diets. One osteoporotic patient was not on combined calcium-vitD supplementation as she could not tolerate the large size of tablets. No patients were on vitamin D only supplementation.